JUC E MMC: POLARIDADE POLÍTICO-RELIGIOSA EM BELO HORIZONTE (Revista de História Regional, 2007)
This article presents a study of the discrepancies between catholic sectors in BH in the 50s and 60s taking the Juventude Universitária Católica (JUC) and the Movimento por um Mundo Cristão (MMC) as basic references. After evaluation the reasons of the politics reversal of both movements, I take into account Hertzs opponent incompatibility law aiming at the enlargement of our understanding of the political and religious divisions from that period.